The New Great American Writers Cookbook - Wells, Dean Faulkner (Book collections on Project MUSE., 2003)
Cookery -- American Literature--> Published in 1981, The Great American Writers Cookbook was a treasure trove of recipes submitted by the country's most celebrated authors. This all-new collection, a fine follow-up for a new era, features recipes that range from peanut butter sandwiches to eggplant caviar, with dishes-and anecdotes-offered by writers of every imaginable stripe, ethnicity, region, and culture in America. Contemporary novelists such as National Book Award winners Jonathan Franzen and the late, great Bernard Malamud share space with columnists Dave Barry, P.J. O'Rourke, and.